Anaesthetic Practices and Maternal Outcome in Rising Placenta Accreta Spectrum in Tertiary Care Hospital - Sumbal Rana , Ali Arslan Munir , Qudsia Anjum Quraishi , Amim Muhammad Akhtar , Erum Pervaiz , Humna Syed (Journal of Rawalpindi Medical College, 2020)
Objective: This study was carried out to determine whether the rate of abnormal placentation is increasing in concurrence with the cesarean section and to assess risk factors and outcomes with multidisciplinary team interventions and anesthetic practices. Study design: Prospective cohort study. Material & Methods: A study was conducted in the department of anaesthesia from January 2014 to December 2017. All candidates under the spectrum of placenta accreta were observed for maternal age, parity, mode of anesthesia, blood loss, and outcome. Results: Out of 109 patients, the preoperative diagnosis of PAS was made up of 100 (91.74%) and intraoperative diagnosis of 9 (08. 26%) patients. According to the mode of anesthesia, 100 (91.74%) patients received GA, and 09 (08.26%) patients received spinal anesthesia. In 06 (05.49%) patients, spinal was converted to GA. Perioperative CPR was done in 05 (04.58%) cases. Out of 109 cases, 83 survived uneventfully, and 21 developed complications. 05 patients expired in the following days. (01 immediately postoperative period, 02 in 1st 24 hours and 02 in 1st 48 hours. Conclusion The rate of placenta accreta increased in conjunction with cesarean deliveries; the most important risk factors were previous cesarean delivery, placenta previa, and advanced maternal age and outcomes improved in a multidisciplinary team intervention.